Hydraulic head loss at the interface between uniform sands of different sizes - Leatherwood, Frank N., author; Peterson, Dean F., Jr., author; American Geophysical Union, publisher (Colorado State University. Libraries, 1954)
The hydraulic head loss for flow occurring at an interface between sands or gravels of different sizes was studied by experiment. Dimensional analysis was used In formulating the experiments and in analyzing the data which led to a simple relationship in which the hydraulic head loss at the interface is a function of the mean diameter of the smaller-sized sand or gravel, the Reynolds number for the flow through the smaller-sized gravel, and an empirical constant which appears to depend principally on the mean size and size distribution characteristics of the two sizes of sand or gravel. The experiments provided an opportunity to observe the action of sands or gravels used as filters and observations confirmed the opinion of Terzaghi and others that for uniform-sized sands the ratio of the mean diameter of the filtering sand to that of the sand to be filtered must not exceed approximately five in order that the smaller-sized material be excluded from the pores of the larger-sized material.
Reprint from Transactions, American Geophysical Union, V. 35, Number 4, August 1954.
Keywords: Hydraulics; Porosity